2017
DOI: 10.1021/acs.jproteome.6b00164
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Metaboproteomics of Burkitt’s and Diffuse Large B-Cell Lymphoma Cell Lines and Primary Tumor Tissues Reveals Distinct Differences in Pyruvate Content and Metabolism

Abstract: Burkitt's lymphoma (BL) and diffuse large B-cell lymphoma (DLBCL) are pathologically and clinically distinct subtypes of aggressive non-Hodgkin B-cell lymphoma. To learn more about their biology, we employed metabolomic and proteomic methods to study both established cell lines as well as cryopreserved and formalin-fixed paraffin-embedded (FFPE) tissue sections of BL and DLBCL. Strikingly, NMR analyses revealed DLBCL cell lines to produce and secrete significantly (p = 1.72 × 10) more pyruvic acid than BL cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…A recent comparative study revealed that BL cells upregulate 1C metabolism [13]. In fact, targeting 1C-coupled folate cycle with antifolates (e.g., methotrexate) has been exploited in BL therapy for decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent comparative study revealed that BL cells upregulate 1C metabolism [13]. In fact, targeting 1C-coupled folate cycle with antifolates (e.g., methotrexate) has been exploited in BL therapy for decades.…”
Section: Discussionmentioning
confidence: 99%
“…MYC impacts many facets of tumor cell metabolism, such as glycolysis, glutaminolysis, and lipid and nucleotide synthesis, and thus affords metabolic flexibility to cancer cells in unfavorable conditions [12]. In a recent, unbiased metabolomic-proteomic screen, BL cells have been shown to markedly upregulate one-carbon (1C) metabolism pathway [13]. One-carbon metabolism comprises of a series of reactions initiated by the folate cycle, which is essential for de novo nucleotide synthesis and regeneration of mitochondrial NADH, NADPH, and ATP [14].…”
Section: Introductionmentioning
confidence: 99%
“…SWATH-MS combines the advantages of untargeted shotgun proteomics by covering hundreds to thousands of protein groups in a single analysis and selected reaction monitoring mass spectrometry by yielding highly reproducible and consistent data. This was recently demonstrated for a comparative analysis of cryopreserved and FFPE tissue sections of Burkitt's lymphoma and DLBCL with more than 90% of the proteins that differed significantly between these two lymphomas showing the same direction of regulation regardless of tissue preservation 17 . Using a reference point insensitive regularized regression method with variable selection 18,19 , we report here the identification of an eight-protein signature that yields not only excellent correlation with GCB predictor scores derived from both Affymetrix GeneChip and NanoString nCounter gene expression data but also carries the advantage of being transferable to other analytical platforms as long as the abundance of the signature proteins can be measured within the linear dynamic ranges of the respective methods.…”
mentioning
confidence: 87%
“…However, authors indicated that application of hot water seems to be a shorter, safer, and easier one. Nonetheless, in proteomics, the most commonly used deparaffinization method is based on xylene [27,33,34].…”
Section: Type Of the Deparaffinizationmentioning
confidence: 99%